Design and setup of a jet-based technology for localized small scale Plasma electrolytic Polishing. (March 2022) - Quitzke, Susanne; Kröning, Oliver; Safranchik, Daniel; Zeidler, Henning; Danilov, Igor; Martin, André; Böttger-Hiller, Falko; Essel, Shai; Schubert, Andreas
Abstract: Plasma electrolytic Polishing (PeP) represents an innovative technique for finish-machining of complex parts and micro features. The applicability is usually restricted by limitations of the electric power provided by the process energy source (PES). Besides, addressing locally confined areas or single micro features is not possible, since the whole workpiece or a part of it is immersed into an electrolyte bath and thus machined. To overcome this, the development and verification of an alternative process arrangement for localized PeP is presented in this study. The immersion-based PeP was transferred to a small-scale jet-based process (Jet-PeP). It is shown that Jet-PeP allows for local and adapted treatment of AISI 316 L. For the realization of the Jet-PeP technology a specific PES, which provides the required electric energy with process-specific characteristics, was developed and implemented into a novel prototype rig. The shape of the electrolyte jet resulting from the chosen flow rate and nozzle diameter was simulated and the maximum expected current for process initiation was determined. For the functional verification, a planar workpiece surface was polished with various voltages. Surface roughness was measured before and after Jet-PeP. The results indicate localized polishing effects and significant reductions in roughness.